2011
DOI: 10.1002/crat.201100125
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of orientation microscopy in SEM and TEM

Abstract: Orientation microscopy (OM) refers to techniques for reconstruction of microstructures based on the spatially resolved measurement of individual crystallographic phases and orientations. This review gives an overview on different techniques of OM in the scanning and transmission electron mi-croscope. All rely on the automated evaluation of electron diffraction patterns. The most popular technique is based on electron backscatter diffraction (EBSD) in the SEM. In the TEM several techniques are available which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 51 publications
0
88
0
1
Order By: Relevance
“…The spatial resolution of the NBD orientation mapping is limited by the combination of several effects, namely, the spot size of the focused electron beam, the convergence angle and the sample thickness [42], it can reach values down to 1 nm [27,32]. For indexing of the NBD patterns, alignment of a certain zone axis with respect to the incident beam is not required.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…The spatial resolution of the NBD orientation mapping is limited by the combination of several effects, namely, the spot size of the focused electron beam, the convergence angle and the sample thickness [42], it can reach values down to 1 nm [27,32]. For indexing of the NBD patterns, alignment of a certain zone axis with respect to the incident beam is not required.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Crystals that light up in each DF image are in a Bragg condition. By using the intensities of each pixel in the complete stack of DF images, the spot diffraction pattern from a small region can be reconstructed [36,37]. This region can ultimately go down to the pixel size of the DF image.…”
Section: Microstructural Characterisationmentioning
confidence: 99%
“…In the present case a stack of dark field images is recorded by precession and using the most prominent diffraction rings appearing in the present material. Virtual diffraction patterns from smaller regions can then be reconstructed with the conical dark field TEM technique [36,37]. Fig.…”
Section: Conical Dark Field Temmentioning
confidence: 99%
“…The experimental results showed that the evolution of low angle misorientations with the increase in plastic strain was well represented by including a misorientation range of 2°-15° (see section 3.5) and the angular resolution of an EBSD system which uses a Hough transform to detect lines in the patterns is less than 1° [31] , so with proper EBSD system optimization it is possible to determine all misorientations above 2° absolutely. For these reasons a misorientation of 2° was taken as the lower limit of a subgrain boundary while misorientations >15° were regarded as high angle boundaries [17,22,[32][33][34] .…”
Section: Lamfmentioning
confidence: 99%